Impact of social distancing from the COVID-19 pandemic on the immuno-inflammatory response of older adults - Beletato Nery, G; Rodrigues de Araujo, CA; da Silva, GB; Bittar, H; Pacheco Bordallo, V; Amaral, JB; Hardt, M; Marti, L; Birbrair, A; Jiménez, Manuel; Ferreira Bastos, M; Silva Nali, LH; et al. (BMC Geriatrics, 2025)
Background: Older adults, as the population considered at increased risk for severe COVID-19, were the most impacted by social isolation. Thus, this study aimed to assess the salivary immune/inflammatory response of older adults before and during the COVID-19 pandemic. Methods: A cohort of 11 older adults (mean age 66.8 ± 6.1) was followed at three different time points: before (S1) and after 6 (S2) and 20 months (S3) of the beginning of the COVID-19 pandemic in Brazil. Unstimulated saliva samples were obtained to assess the levels of antibodies (secretory IgA, IgG and IgM) by ELISA and cytokines (IL-2, IL-5, IL-6, IL-8 and IL-10, TSLP, IFN-γ, TNF-α) by multiplex analysis. Significant differences were evaluated using the Kruskal–Wallis test with Dunn's post-test. Results: None volunteer presented periodontal disease or caries. All volunteers received at least two doses of the COVID-19 vaccines after S2 and before S3. A tendency to increase salivary levels of SIgA and IgM at S2 and of IgG at S3 were observed compared to the values found at S1 and S2. Significantly decreased levels of IL-2 and IL-5 were found at S2 and S3 (p < 0.001) time points. Lower levels of IFN-γ were found at S2 as compared to the values observed at S1 (p < 0.01). A significant decrease in the IFN-γ/IL-10 ratio was found at S2 (p < 0.01). When assessing the Th1/Th2 ratios, a significant decrease was found in the IFN-γ/TSLP ratio at S2 (p < 0.001) and S3 (p < 0.001) when compared to the values at S1. In addition, a significant increase was observed in the TNF-α/IL-5 ratio at S2 (p < 0.001) and S3 (p < 0.001) in comparison to the values at S1. In a similar way, an increase in the TNF-α/IL-6 ratio (Fig. 5E) was observed at S3 (p < 0.001) when compared to the values at S1. Conclusions: Overall, this study provides valuable insights into the impact of COVID-19-induced social isolation on immune/inflammatory responses in the upper airway mucosa, particularly those present in oral cavity, of older adults. It demonstrates that a controlled shift in Th1 and Th2 immune responses, both during infection and post-vaccination, can create favorable conditions to combat viral infections without exacerbating the immune response or worsening the pathology.
Keywords: cytokines; Interferon; Interleukin; mucosal immunity; SARS-CoV-2; saliva